2006
DOI: 10.1007/s11427-005-0071-5
|View full text |Cite
|
Sign up to set email alerts
|

Production of porcine cloned transgenic embryos expressing green fluorescent protein by somatic cell nuclear transfer

Abstract: The increases of H2O2 concentrations in plant cells often occur under biotic and abiotic stress conditions (e.g. light, environmental stresses and plant hormone abscisic acid). Atmospheric H202 as an ancient signal molecule not only plays the key role in inducing evolution of oxygenic photosynthesis, but also modulates many physiological events, such as stomatal movement, hypersensitive responses, programmed cell death and gene expressions. H2O2 levels in cells must sustain a fine equilibrium between productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 26 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…For H 2 O 2 detection, the treated samples were immersed in 1 mg/mL fresh DAB solution (pH 5.8) (prepared in 10 mmol/L phosphate buffer, pH 3.8) and incubated in dark at 28 °C for 8 h. The stained samples were then bleached in 80% ethanol and boiled for several minutes (2–5 min), then dropped for staining by concentrated ethanol and kept in 4 °C, as described by Cheng and Song [50]. …”
Section: Methodsmentioning
confidence: 99%
“…For H 2 O 2 detection, the treated samples were immersed in 1 mg/mL fresh DAB solution (pH 5.8) (prepared in 10 mmol/L phosphate buffer, pH 3.8) and incubated in dark at 28 °C for 8 h. The stained samples were then bleached in 80% ethanol and boiled for several minutes (2–5 min), then dropped for staining by concentrated ethanol and kept in 4 °C, as described by Cheng and Song [50]. …”
Section: Methodsmentioning
confidence: 99%
“…More in vitro studies from our laboratory demonstrated that the promoter could drive the expression of GFP or CAT as reporter genes in each direction with the presence of MDV pp24/pp38 hetero-dimer. The pp24/38 dimer was able to bind to the promoter and worked in-trans as a transcriptional factor to enhance the transcription activity [9], [41]. In this study, use recombinant plasmid transient transfected CEF as well as in recombinant MDV infected CEF, it was demonstrated that different foreign genes could be expressed simultaneously under control of the bi-directional promoter.…”
Section: Discussionmentioning
confidence: 95%
“…The results clearly indicated that the MDV endogenous bi-directional promoter of only 305 bp could effectively drive two foreign genes expressed in two directions. As mentioned above, the bi-directional promoter is located between pp38 and 1.8kb mRNA family transcription start sites and pp38/pp24 dimer could work as trans-acting transcriptional factor to strongly enhance its promoter activity [8], [9], [41], the bi-directional promoter may have some advantages in expression of two foreign genes in the early stage of MDV infection. This is because pp38 is an early gene related to MDV early B-lymphocyte cytolytic infection [44], and pp38/pp24 dimers should be available in the early stage of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The matured oocytes at the stage of metaphase II with the visualized first polar body are usually used as sources of cytoplasts for cloning (Hardarson et al, 2000). In pigs, the optimal duration of in vitro maturation of oocytes varies according to different studies in the range from 24 to 44 hours (Zhang et al, 2006;Sugimura et al, 2010).…”
Section: Oocyte Maturationmentioning
confidence: 99%